Society and the land : contemporary Iban society, development policy, and the value of native customary rights land in Sarawak, Malaysia - Tomomi, Matsubara. (Universiti Malaysia Sarawak, (UNIMAS), 2003)
This thesis takes a case study of Rh. Kemarau in Machan, Sibu District, Sarawak, Malaysia, in order to examine firstly the influence of the contemporary development policy in Sarawak on the Iban longhouse and secondly the potential economic value of their Native Customary Rights land under the present circumstances.